A iniciação científica e o exercício da docência na educação básica: ressignificações da experiência de professores iniciantes - Braccini, Marja Leão (Universidade do Vale do Rio dos Sinos, 2012)
This study aims at comprehending whether the undergraduate students in degree courses who experienced as a Scientific Initiation Scholarships recognize that this condition influences in their posterior teaching condition in the basic education. It is possible to highlight as main objectives: (1) Identify the major sources of the teaching knowledge construction for teachers that used to work with scientific initiation; (2) Identify the main learning experiences acquired during the scientific initiation; (3) Comprehend whether the learning experiences obtained during the initiation to the research are significant to the teaching; (4) Understand how mentor teachers of SIS perceive the initiation to the research as part of the initial training for teaching. This investigation is based on the principles of the qualitative research and semi-structured interviews are being conducted with six teachers, graduates in degree courses and also from Si Programs and with the university professors who were their advisors. The data were organized in two large dimensions: Scientific Initiation and knowledge of research and knowledge of teaching. The dimension Scientific Initiation was divided in the categories – motivations and learning. And the second dimension has the categories: Scientific Initiation and the teachers training; reflexive/research teachers; learning with research. The study addresses, either, some highlights from the advisors, and the challenges lived by the graduates from the early carrier, stage that they are. The literature review and the findings from the analysis of the speeches of our partners have been helping us understand that the research, as a component of the teacher training, can’t be seen in isolation. It will be in the surroundings of the objective conditions of the teaching work. However, when considering the Scientific Initiation as a significant experience in the training of undergraduates, we have seen that this condition may have an impact on the teaching knowledge, contributing to the qualification of the education and the teaching work.
Keywords: Scientific initiation; Formal schooling; Teaching work; Research and teaching; Educação básica; Professores iniciantes; Pesquisa e ensino; Formação de professores; Iniciação científica; ACCNPQ::Ciências Humanas::Educação